A kind of grease composition for bearing and preparation method thereof

Through oxidation, graphene nanoparticles and heterocyclic compounds are used to solve the problem of decreased performance of lubricating fat in high temperature environments, and significantly improved the mechanical performance, thermal stability and abrasion resistance of grease.

CN118879381BActive Publication Date: 2025-01-28GUANGDONG AIR FRANCE IND CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410917683.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-09
Publication Date
2025-01-28
Estimated Expiration
2044-07-09

AI Technical Summary

Technical Problem

In high temperature environments, the light components in the grease evaporate, the heavy components oxidize, soften or coke, resulting in a degradation of lubricating performance, intensifying wear of friction parts, increasing noise, and even jamming failures.

Method used

The nano particles composed of graphene composed of graphene oxidation can promote the formation of metastatic membrane and improve the boundary lubrication of the friction system. The ionic ionic enters the graphene -like structure through the action of the ionic ion.

Benefits of technology

The mechanical performance, thermal stability and wear resistance of lubricating fat are significantly improved, solve the problem of being easily accumulated during the friction process, improved the interface state, and improved the overall performance of the grease.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004935630940000101
    Figure BDA0004935630940000101
  • Figure BDA0004935630940000111
    Figure BDA0004935630940000111
Patent Text Reader

Abstract

The present invention relates to a grease composition for bearings and a preparation method thereof, and belongs to the technical field of grease. A grease composition for bearings comprises the following components: a fluorine-containing base oil, a thickener and a modified filler additive; the thickener is a mixture of polytetrafluoroethylene and tetrafluoroethylene-hexafluoropropylene copolymer; the present invention promotes the formation of a transfer film through nanoparticles composed of zirconium oxide modified graphene, improves the boundary lubrication of the friction system, makes the grease wear-resistant, and zirconium ions promote heterocyclic compounds to enter and adhere to the graphene layered structure through coordination, and the eugenol group of the heterocyclic compound grafted with oxygen-containing groups combines with the TBA fluorine element to improve the oil solubility, thereby significantly improving the mechanical properties, thermal stability and wear resistance of the grease.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lubricating grease and relates to a lubricating grease composition for bearings and a preparation method thereof. Background Art

[0002] Grease is widely used in industrial machinery, transportation machinery, aerospace, electronic information products and various military equipment. With the continuous improvement of my country's industrialization level, the lubrication parts of some advanced large-scale equipment and precision instruments are facing the challenge of increasing operating temperatures. Some equipment even has an operating temperature of more than 400°C in a short period of time. The lubrication problem in high-temperature equipment bearings has become an important problem that equipment management and maintenance personnel often need to face. When grease is working in a high-temperature and long-term environment, the light components in the grease will evaporate rapidly, and the heavy components may oxidize, soften and even coke at high temperatures, which will directly affect the lubrication performance of the grease, and may cause increased wear of the friction parts, increased noise, and even jamming and other faults, thereby affecting the normal operation of the equipment.

[0003] Graphene, a two-dimensional material obtained from graphite by mechanical exfoliation technology, has attracted widespread attention due to its unique physical and chemical properties, such as high carrier mobility, large specific surface area, excellent electrical and thermal conductivity, and low interlayer shear resistance. In the field of tribology, graphene has shown great potential for application in greases due to its excellent tribological properties. However, although graphene has excellent friction reduction and anti-wear capabilities, its agglomeration and defects may lead to instability in its friction performance. When graphene is directly added to grease and used in the operation of bearings, graphene is easily accumulated at the bottom of the wear scar during the friction process, deteriorating the interface state and increasing the roughness of the interface, which further limits the application of graphene in greases. Summary of the invention

[0004] The object of the present invention is to provide a grease composition for bearings and a preparation method thereof. The present invention promotes the formation of a transfer film by using nanoparticles composed of zirconium oxide-modified graphene, improves the boundary lubrication of the friction system, and makes the grease wear-resistant. The zirconium ions promote the entry and attachment of heterocyclic compounds to the graphene layered structure through coordination. The eugenol group of the heterocyclic compound grafted with oxygen-containing groups combines with the TBA fluorine element to improve the oil solubility, thereby significantly improving the mechanical properties, thermal stability and wear resistance of the grease.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] A bearing grease composition comprises the following components by weight: 60-72 parts of fluorine-containing base oil, 24-30 parts of thickener, and 4-5 parts of modified filler additive;

[0007] As a preferred technical solution of the present invention, the thickener is formed by mixing polytetrafluoroethylene with a particle size of 1-2 μm and tetrafluoroethylene-hexafluoropropylene copolymer with a particle size of 0.05-0.06 μm in a mass ratio of 1.0-1.3:2.2-2.8.

[0008] As a preferred technical solution of the present invention, the fluorine-containing base oil is one or more of D-type perfluoropolyether base oil, K-type perfluoropolyether base oil, Y-type perfluoropolyether base oil and Z-type perfluoropolyether base oil.

[0009] As a preferred technical solution of the present invention, the preparation method of the modified filler additive comprises the following steps:

[0010] Step S1: After mixing graphene, zirconium oxychloride octahydrate, an additive and deionized water, ammonia water is added for heating and stirring, and after cooling to room temperature, solids are taken out by centrifugation for washing, and dried in an oven to obtain a mixed filler;

[0011] Step S2: placing the mixed filler in anhydrous ethanol and stirring to mix, adding a heterocyclic compound and ultrasonically treating it, adding eugenol and an initiator and mixing them, and then irradiating them with ultraviolet light, centrifuging to obtain a solid, washing it, and drying it in an oven to obtain a prefabricated filler;

[0012] Step S3: Place the prefabricated filler in anhydrous ethanol and stir to mix, add glacial acetic acid and TBA, heat and stir, remove the solvent by rotary evaporation, and place in an oven to dry to obtain a modified filler additive.

[0013] As a preferred technical solution of the present invention, in step S1, the heating and stirring is stirring at a temperature of 180-200°C for 5-6h; the washing is washing with deionized water until neutral; and the drying is drying at a temperature of 80-85°C to constant weight.

[0014] As a preferred technical solution of the present invention, in step S1, the usage ratio of graphene, zirconium oxychloride octahydrate, additive, deionized water and ammonia water is 6.6-7.2:4.0-4.3:0.20-0.26:35-40:3.6-4.2; the mass fraction of ammonia water is 28%; and the additive is ethylene glycol.

[0015] As a preferred technical solution of the present invention, in step S2, the ultrasonic mixing is ultrasonic mixing at a frequency of 300-400W for 10-15min; the ultraviolet irradiation is ultraviolet irradiation at a temperature of 30-35°C with 365nm and stirring for 5-6h; the washing is washing 3 times with anhydrous ethanol; and the drying is drying to constant weight.

[0016] As a preferred technical solution of the present invention, in step S2, the mass ratio of the mixed filler, anhydrous ethanol, heterocyclic compound, eugenol and initiator is 15-18:40-50:4-6:3.0-3.9:0.14-0.16; the heterocyclic compound is 5-amino-2-mercapto-1,3,4-thiadiazole; and the initiator is photoinitiator 1173.

[0017] As a preferred technical solution of the present invention, in step S3, the heating and stirring is stirring at a temperature of 70-75°C for 8-10h; and the drying is drying at a temperature of 80-90°C to constant weight.

[0018] As a preferred technical solution of the present invention, in step S3, the mass ratio of the prefabricated filler, anhydrous ethanol, glacial acetic acid and TBA is 20-22:45-60:0.15-0.20:6.5-8.0; and the TBA is 3,4,5-trifluorobenzaldehyde.

[0019] As a preferred technical solution of the present invention, a method for preparing a bearing grease composition comprises the following steps:

[0020] Step 1: After ultrasonically mixing the fluorine-containing base oil and the modified filler additive, a thickener is added and stirred to obtain a mixed liquid;

[0021] Step 2: homogenizing and grinding the mixed liquid to obtain a grease composition.

[0022] As a preferred technical solution of the present invention, in step one, the ultrasonic mixing is performed at a temperature of 40-50°C and a frequency of 80-120W for 1.0-1.5h; the stirring mixing condition is performed at a temperature of 50-60°C and a stirring condition for 1.5-2.0h.

[0023] As a preferred technical solution of the present invention, in step 2, the grinding time is 1.5-2.0h.

[0024] Beneficial effects of the present invention:

[0025] The present invention promotes the formation of transfer film by using nanoparticles composed of zirconium oxide modified graphene, improves the boundary lubrication of the friction system, and makes the grease wear-resistant. The zirconium ions promote the entry and attachment of heterocyclic compounds to the graphene layered structure through coordination. The eugenol group of the heterocyclic compound grafted with oxygen-containing groups combines with the TBA fluorine element to improve the oil solubility, thereby significantly improving the mechanical properties, thermal stability and wear resistance of the grease. DETAILED DESCRIPTION

[0026] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.

[0027] Example 1

[0028] A bearing grease composition comprises the following components by weight: 60 parts of fluorine-containing base oil, 24 parts of thickener, and 4 parts of modified filler additive; the fluorine-containing base oil is a K-type perfluoropolyether base oil; the thickener is a mixture of polytetrafluoroethylene with a particle size of 1 μm and tetrafluoroethylene-hexafluoropropylene copolymer with a particle size of 0.05 μm in a mass ratio of 1.0:2.2;

[0029] The preparation method of the modified filler additive comprises the following steps:

[0030] Step S1: After mixing graphene, zirconium oxychloride octahydrate, an additive and deionized water, ammonia water is added for heating and stirring, and after cooling to room temperature, solids are taken out by centrifugation for washing, and dried in an oven to obtain a mixed filler;

[0031] In step S1, the heating and stirring is stirring at a temperature of 180° C. for 5 hours; the washing is washing with deionized water until neutral; the drying is drying at a temperature of 80° C. until constant weight; the usage ratio of the graphene, zirconium oxychloride octahydrate, additive, deionized water and ammonia water is 6.6:4.0:0.20:35:3.6; the mass fraction of the ammonia water is 28%; the additive is ethylene glycol;

[0032] Step S2: placing the mixed filler in anhydrous ethanol and stirring to mix, adding a heterocyclic compound and ultrasonically treating it, adding eugenol and an initiator and mixing them, and then irradiating them with ultraviolet light, centrifuging to obtain a solid, washing it, and drying it in an oven to obtain a prefabricated filler;

[0033] In step S2, the ultrasonic mixing is performed at a frequency of 300W for 10 minutes; the ultraviolet irradiation is performed at a temperature of 30°C and a temperature of 365nm with stirring for 5 hours; the washing is performed 3 times with anhydrous ethanol; the drying is performed to a constant weight; the mass ratio of the mixed filler, anhydrous ethanol, heterocyclic compound, eugenol and initiator is 15:40:4:3.0:0.14; the heterocyclic compound is 5-amino-2-mercapto-1,3,4-thiadiazole; the initiator is photoinitiator 1173;

[0034] Step S3: Place the prefabricated filler in anhydrous ethanol and stir to mix, add glacial acetic acid and TBA, heat and stir, remove the solvent by rotary evaporation, and place in an oven to dry to obtain a modified filler additive.

[0035] In step S3, the heating and stirring is stirring at 70°C for 8 hours; the drying is drying at 80°C to constant weight; the mass ratio of the prefabricated filler, anhydrous ethanol, glacial acetic acid and TBA is 20:45:0.15:6.5; the TBA is 3,4,5-trifluorobenzaldehyde;

[0036] A method for preparing a bearing grease composition comprises the following steps:

[0037] Step 1: After ultrasonically mixing the fluorine-containing base oil and the modified filler additive, a thickener is added and stirred to obtain a mixed liquid;

[0038] In step 1, the ultrasonic mixing is performed at 40°C and 80W frequency for 1.0 h; the stirring mixing is performed at 50°C and 1.5 h;

[0039] Step 2: homogenizing and grinding the mixed liquid to obtain a grease composition;

[0040] In step 2, the grinding time is 1.5 hours.

[0041] Example 2

[0042] A bearing grease composition comprises the following components by weight: 64 parts of fluorine-containing base oil, 26 parts of thickener, and 4.3 parts of modified filler additive; the fluorine-containing base oil is a K-type perfluoropolyether base oil; the thickener is a mixture of polytetrafluoroethylene with a particle size of 1.5 μm and tetrafluoroethylene-hexafluoropropylene copolymer with a particle size of 0.05 μm in a mass ratio of 1.1:2.4;

[0043] The preparation method of the modified filler additive comprises the following steps:

[0044] Step S1: After mixing graphene, zirconium oxychloride octahydrate, an additive and deionized water, ammonia water is added for heating and stirring, and after cooling to room temperature, solids are taken out by centrifugation for washing, and dried in an oven to obtain a mixed filler;

[0045] In step S1, the heating and stirring is stirring at a temperature of 185° C. for 5.5 hours; the washing is washing with deionized water until neutral; the drying is drying at a temperature of 82° C. until constant weight; the usage ratio of the graphene, zirconium oxychloride octahydrate, additive, deionized water and ammonia water is 6.8:4.1:0.22:37:3.8; the mass fraction of the ammonia water is 28%; the additive is ethylene glycol;

[0046] Step S2: placing the mixed filler in anhydrous ethanol and stirring to mix, adding a heterocyclic compound and ultrasonically treating it, adding eugenol and an initiator and mixing them, and then irradiating them with ultraviolet light, centrifuging to obtain a solid, washing it, and drying it in an oven to obtain a prefabricated filler;

[0047] In step S2, the ultrasonic mixing is performed at a frequency of 330W for 12 minutes; the ultraviolet irradiation is performed at a temperature of 32°C and 365nm ultraviolet irradiation with stirring for 5.5 hours; the washing is performed 3 times with anhydrous ethanol; the drying is performed to a constant weight; the mass ratio of the mixed filler, anhydrous ethanol, heterocyclic compound, eugenol and initiator is 16:43:4.7:3.3:0.15; the heterocyclic compound is 5-amino-2-mercapto-1,3,4-thiadiazole; the initiator is photoinitiator 1173;

[0048] Step S3: Place the prefabricated filler in anhydrous ethanol and stir to mix, add glacial acetic acid and TBA, heat and stir, remove the solvent by rotary evaporation, and place in an oven to dry to obtain a modified filler additive.

[0049] In step S3, the heating and stirring is stirring at 72° C. for 8.5 hours; the drying is drying at 83° C. to constant weight; the mass ratio of the prefabricated filler, anhydrous ethanol, glacial acetic acid and TBA is 20.7:50:0.17:7; the TBA is 3,4,5-trifluorobenzaldehyde;

[0050] A method for preparing a bearing grease composition comprises the following steps:

[0051] Step 1: After ultrasonically mixing the fluorine-containing base oil and the modified filler additive, a thickener is added and stirred to obtain a mixed liquid;

[0052] In step 1, the ultrasonic mixing is performed at 43°C and 95W for 1.2 hours; the stirring mixing is performed at 53°C and 1.7 hours;

[0053] Step 2: homogenizing and grinding the mixed liquid to obtain a grease composition;

[0054] In step 2, the grinding time is 1.7 h.

[0055] Example 3

[0056] A bearing grease composition comprises the following components by weight: 68 parts of fluorine-containing base oil, 28 parts of thickener, and 4.7 parts of modified filler additive; the fluorine-containing base oil is a K-type perfluoropolyether base oil; the thickener is a mixture of polytetrafluoroethylene with a particle size of 1.5 μm and tetrafluoroethylene-hexafluoropropylene copolymer with a particle size of 0.06 μm in a mass ratio of 1.2:2.6;

[0057] The preparation method of the modified filler additive comprises the following steps:

[0058] Step S1: After mixing graphene, zirconium oxychloride octahydrate, an additive and deionized water, ammonia water is added for heating and stirring, and after cooling to room temperature, solids are taken out by centrifugation for washing, and dried in an oven to obtain a mixed filler;

[0059] In step S1, the heating and stirring is stirring at a temperature of 193° C. for 5.5 hours; the washing is washing with deionized water until neutral; the drying is drying at a temperature of 83° C. until constant weight; the usage ratio of the graphene, zirconium oxychloride octahydrate, additive, deionized water and ammonia water is 7:4.2:0.24:38:4; the mass fraction of the ammonia water is 28%; the additive is ethylene glycol;

[0060] Step S2: placing the mixed filler in anhydrous ethanol and stirring to mix, adding a heterocyclic compound and ultrasonically treating it, adding eugenol and an initiator and mixing them, and then irradiating them with ultraviolet light, centrifuging to obtain a solid, washing it, and drying it in an oven to obtain a prefabricated filler;

[0061] In step S2, the ultrasonic mixing is performed at a frequency of 360W for 13 minutes; the ultraviolet irradiation is performed at a temperature of 33°C and 365nm ultraviolet irradiation with stirring for 5.5 hours; the washing is performed 3 times with anhydrous ethanol; the drying is performed to a constant weight; the mass ratio of the mixed filler, anhydrous ethanol, heterocyclic compound, eugenol and initiator is 17:47:5.3:3.6:0.155; the heterocyclic compound is 5-amino-2-mercapto-1,3,4-thiadiazole; the initiator is photoinitiator 1173;

[0062] Step S3: Place the prefabricated filler in anhydrous ethanol and stir to mix, add glacial acetic acid and TBA, heat and stir, remove the solvent by rotary evaporation, and place in an oven to dry to obtain a modified filler additive.

[0063] In step S3, the heating and stirring is stirring at 73°C for 9.3h; the drying is drying at 87°C to constant weight; the mass ratio of the prefabricated filler, anhydrous ethanol, glacial acetic acid and TBA is 21.3:55:0.18:7.5; the TBA is 3,4,5-trifluorobenzaldehyde;

[0064] A method for preparing a bearing grease composition comprises the following steps:

[0065] Step 1: After ultrasonically mixing the fluorine-containing base oil and the modified filler additive, a thickener is added and stirred to obtain a mixed liquid;

[0066] In step 1, the ultrasonic mixing is performed at 47°C and 107W for 1.3 hours; the stirring mixing is performed at 57°C for 1.8 hours;

[0067] Step 2: homogenizing and grinding the mixed liquid to obtain a grease composition;

[0068] In step 2, the grinding time is 1.8 hours.

[0069] Example 4

[0070] A bearing grease composition comprises the following components by weight: 72 parts of fluorine-containing base oil, 30 parts of thickener, and 5 parts of modified filler additive; the fluorine-containing base oil is a K-type perfluoropolyether base oil; the thickener is a mixture of polytetrafluoroethylene with a particle size of 2 μm and tetrafluoroethylene-hexafluoropropylene copolymer with a particle size of 0.06 μm in a mass ratio of 1.3:2.8;

[0071] The preparation method of the modified filler additive comprises the following steps:

[0072] Step S1: After mixing graphene, zirconium oxychloride octahydrate, an additive and deionized water, ammonia water is added for heating and stirring, and after cooling to room temperature, solids are taken out by centrifugation for washing, and dried in an oven to obtain a mixed filler;

[0073] In step S1, the heating and stirring is stirring at a temperature of 200° C. for 6 hours; the washing is washing with deionized water until neutral; the drying is drying at a temperature of 85° C. until constant weight; the usage ratio of the graphene, zirconium oxychloride octahydrate, additive, deionized water and ammonia water is 7.2:4.3:0.26:40:4.2; the mass fraction of the ammonia water is 28%; the additive is ethylene glycol;

[0074] Step S2: placing the mixed filler in anhydrous ethanol and stirring to mix, adding a heterocyclic compound and ultrasonically treating it, adding eugenol and an initiator and mixing them, and then irradiating them with ultraviolet light, centrifuging to obtain a solid, washing it, and drying it in an oven to obtain a prefabricated filler;

[0075] In step S2, the ultrasonic mixing is performed at a frequency of 400W for 15 minutes; the ultraviolet irradiation is performed at a temperature of 35°C and 365nm ultraviolet irradiation with stirring for 6 hours; the washing is performed 3 times with anhydrous ethanol; the drying is performed to a constant weight; the mass ratio of the mixed filler, anhydrous ethanol, heterocyclic compound, eugenol and initiator is 18:50:6:3.9:0.16; the heterocyclic compound is 5-amino-2-mercapto-1,3,4-thiadiazole; the initiator is photoinitiator 1173;

[0076] Step S3: Place the prefabricated filler in anhydrous ethanol and stir to mix, add glacial acetic acid and TBA, heat and stir, remove the solvent by rotary evaporation, and place in an oven to dry to obtain a modified filler additive.

[0077] In step S3, the heating and stirring is stirring at 75°C for 10 hours; the drying is drying at 90°C to constant weight; the mass ratio of the prefabricated filler, anhydrous ethanol, glacial acetic acid and TBA is 22:60:0.20:8.0; the TBA is 3,4,5-trifluorobenzaldehyde;

[0078] A method for preparing a bearing grease composition comprises the following steps:

[0079] Step 1: After ultrasonically mixing the fluorine-containing base oil and the modified filler additive, a thickener is added and stirred to obtain a mixed liquid;

[0080] In step 1, the ultrasonic mixing is performed at 50°C and 120W frequency for 1.5 hours; the stirring mixing is performed at 60°C and 2.0 hours;

[0081] Step 2: homogenizing and grinding the mixed liquid to obtain a grease composition;

[0082] In step 2, the grinding time is 2.0 h.

[0083] Comparative Example 1

[0084] Compared with Example 2, Comparative Example 1 is different in that zirconium oxychloride octahydrate is not used, and the other components, preparation steps and parameters are the same.

[0085] Comparative Example 2

[0086] Compared with Example 2, Comparative Example 2 is different in that graphene is not used, and the remaining components, preparation steps and parameters are the same.

[0087] Comparative Example 3

[0088] Compared with Example 2, Comparative Example 3 is different in that eugenol is not used, and the other components, preparation steps and parameters are the same.

[0089] Comparative Example 4

[0090] Compared with Example 2, Comparative Example 4 is different in that no heterocyclic compound is used, and the remaining components, preparation steps and parameters are the same.

[0091] Comparative Example 5

[0092] Compared with Example 2, Comparative Example 5 is different in that benzaldehyde is used instead of TBA, and the other components, preparation steps and parameters are the same.

[0093] Comparative Example 6

[0094] Compared with Example 2, Comparative Example 6 is different in that TBA is not used, and the remaining components, preparation steps and parameters are the same.

[0095] The grease compositions prepared in Examples 1-4 and Comparative Examples 1-6 were tested as follows. The test results are shown in Table 1.

[0096] Friction coefficient test: according to SH / T 0762-2005;

[0097] Wear spot diameter test: according to SH / T 0189-2017.

[0098] Table 1

[0099]

[0100]

[0101] From the test results in Table 1, it can be seen that compared with Comparative Examples 1-6, the friction coefficient and wear spot diameter of the grease composition prepared in Examples 1-4 of the present invention are significantly lower than those in Comparative Examples 1-6. The grease composition prepared in the present invention has beneficial wear resistance.

[0102] By comparing Examples 1-4 with Comparative Examples 1-2 and Table 1, it can be seen that the present invention modifies graphene by zirconium oxide, so that zirconium oxide is generated in situ on the graphene layered structure, reducing self-agglomeration to improve its dispersibility in the grease. Under the conditions of the grease, the nanoparticles composed of graphene and zirconium oxide in the additive polymer can promote the formation of a transfer film, improve the boundary lubrication conditions of the friction system, and make the grease have good wear resistance; in addition, the zirconium ions in the mixed filler can promote the entry of heterocyclic compounds through coordination and adhere to the layered structure of graphene through the interaction of amino and thiol groups with the mixed filler, thereby increasing the binding force between organic groups and inorganic compounds and improving the mechanical properties and anti-wear properties of the grease.

[0103] By comparing Examples 1-4 with Comparative Examples 3-6, combined with Table 1, it can be seen that the present invention can improve the friction reduction and antioxidant properties of the additive by using the eugenol group of the oxygen-containing group grafted on the heterocyclic compound on the mixed filler, and can improve the oil solubility of the additive in the base oil by combining with the fluorine element of TBA. The polar hydroxyl group can improve the anti-wear and extreme pressure resistance of the compound. The presence of the benzene ring structure of eugenol and TBA can improve the thermal stability and mechanical properties of the compound, making it more anti-wear; the heterocyclic compound and TBA form a Schiff base compound containing an imine structure, which can improve the wear resistance of the additive and make the dispersion of graphene and zirconium oxide in the grease better, effectively reduce the friction coefficient, and solve the problem that graphene is easily accumulated at the bottom of the wear mark and deteriorates the interface state during the friction process.

[0104] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A grease composition for a bearing, characterized in that: The composition includes the following components by weight: 60-72 parts of fluorine-containing base oil, 24-30 parts of thickener, and 4-5 parts of modified filler additive; The thickener is a mixture of polytetrafluoroethylene and tetrafluoroethylene-hexafluoropropylene copolymer; Wherein, the preparation method of the modified filler additive comprises the following steps: Step S1: After stirring and mixing graphene, zirconium oxychloride octahydrate, an auxiliary agent and deionized water, adding ammonia water, heating and stirring, cooling to room temperature, centrifuging and washing solids, placing in an oven for drying, and obtaining a mixed filler; the usage ratio of the graphene, zirconium oxychloride octahydrate, auxiliary agent, deionized water and ammonia water is 6.6-7.2:4.0-4.3:0.20-0.26:35-40:3.6-4.2; the auxiliary agent is ethylene glycol; Step S2: placing the mixed filler in anhydrous ethanol and stirring and mixing, adding the heterocyclic compound and ultrasonically treating, adding eugenol and an initiator and mixing, and then irradiating with ultraviolet light, centrifuging and washing the solid, and drying in an oven to obtain a prefabricated filler; the mass ratio of the mixed filler, anhydrous ethanol, heterocyclic compound, eugenol and initiator is 15-18:40-50:4-6:3.0-3.9:0.14-0.16; the heterocyclic compound is 5-amino-2-mercapto-1,3,4-thiadiazole; the ultraviolet light irradiation is irradiating with 365nm ultraviolet light at a temperature of 30-35°C and stirring for 5-6h; Step S3: placing the prefabricated filler in anhydrous ethanol and stirring and mixing, adding glacial acetic acid and TBA, heating and stirring, rotary evaporating to remove the solvent, placing in an oven to dry, and obtaining a modified filler additive; the mass ratio of the prefabricated filler, anhydrous ethanol, glacial acetic acid and TBA is 20-22:45-60:0.15-0.20:6.5-8.0; and the TBA is 3,4,5-trifluorobenzaldehyde.

2. A bearing grease composition according to claim 1, characterized in that: The thickener is prepared by mixing polytetrafluoroethylene with a particle size of 1-2 μm and tetrafluoroethylene-hexafluoropropylene copolymer with a particle size of 0.05-0.06 μm in a mass ratio of 1.0-1.3:2.2-2.

8.

3. A bearing grease composition according to claim 1, characterized in that: The fluorine-containing base oil is one or more of a D-type perfluoropolyether base oil, a K-type perfluoropolyether base oil, a Y-type perfluoropolyether base oil and a Z-type perfluoropolyether base oil.

4. A bearing grease composition according to claim 1, characterized in that: In step S1, the heating and stirring is stirring at a temperature of 180-200° C. for 5-6 hours; the washing is washing with deionized water until neutral; and the drying is drying at a temperature of 80-85° C. until constant weight.

5. The bearing grease composition according to claim 1, characterized in that: In step S1, the mass fraction of the ammonia water is 28%.

6. The bearing grease composition according to claim 1, characterized in that: In step S2, the ultrasonic treatment is performed at a frequency of 300-400 W for 10-15 min; the washing is performed 3 times with anhydrous ethanol; and the drying is performed to a constant weight.

7. The bearing grease composition according to claim 1, characterized in that: In step S2 , the initiator is a photoinitiator 1173 .

8. The bearing grease composition according to claim 1, characterized in that: In step S3, the heating and stirring is stirring at a temperature of 70-75°C for 8-10 hours; and the drying is drying at a temperature of 80-90°C to constant weight.

9. A method for preparing a bearing grease composition according to any one of claims 1 to 8, characterized in that: The preparation method comprises the following steps: Step 1: After ultrasonically mixing the fluorine-containing base oil and the modified filler additive, a thickener is added and stirred to obtain a mixed liquid; Step 2: homogenizing and grinding the mixed liquid to obtain a grease composition.

10. The method for preparing a bearing grease composition according to claim 9, characterized in that: In step one, the ultrasonic mixing is performed at a temperature of 40-50°C and a frequency of 80-120W for 1.0-1.5 hours; the stirring mixing condition is performed at a temperature of 50-60°C and a stirring time of 1.5-2.0 hours; in step two, the grinding time is 1.5-2.0 hours.

Citation Information

Patent Citations

  • Facile synthesis of graphene, graphene derivatives and abrasive nanoparticles, and their various uses, including as tribologically-beneficial lubricant additives

    CN103534205A

  • Gear type automobile steering gear lubricating grease composition

    CN107502419A